The monetary transmission mechanism - Peter N. Ireland (Federal Reserve Bank of Boston, 2006)
The monetary transmission mechanism describes how policy-induced changes in the nominal money stock or the short-term nominal interest rate impact real variables such as aggregate output and employment. Specific channels of monetary transmission operate through the effects that monetary policy has on interest rates, exchange rates, equity and real estate prices, bank lending, and firm balance sheets. Recent research on the transmission mechanism seeks to understand how these channels work in the context of dynamic, stochastic, general equilibrium models.
Keywords: E52; 330; Transmissionsmechanismus; Geldpolitik; Geldmenge; Zins; Theorie